2008
DOI: 10.5650/jos.57.15
|View full text |Cite
|
Sign up to set email alerts
|

Large Decrease in Acute Aquatic Toxicity of Linear Alkylbenzene Sulfonate in Hard Water and Seawater by Adding Adsorbent

Abstract: LAS (Linear Alkylbenzene Sulphonate) shows relatively high aquatic toxicity in hard freshwater or seawater. In this paper, we studied the effect of adsorbent on the aquatic toxicity of LAS in hard freshwater and seawater. Daphnia magna and Artemia salina were used for acute aquatic toxicity test in freshwater and seawater, respectively. Kaolin was used as a model adsorbent and toxic surface tension (g tox ) was used as an indicator of toxic condition. Results showed that the values of g tox of LAS to D. magna … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
8
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 9 publications
3
8
0
1
Order By: Relevance
“…The result of 20 mg/L LAS showed the similar behavior to that of 10 mg/L LAS except that each change occurred about 24 to 48 h later than that of 10 mg/L ( ). In our previous studies 3,4) , g tox of LAS on Daphnia magna was about 50 mN/m. Death ratio of 50 % is expected for both 10 mg/L LAS ( ) and 20 mg/L LAS ( ) when surface tension is 50 ~ 60 mN/m, which corresponds to g tox of LAS under biodegradation.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The result of 20 mg/L LAS showed the similar behavior to that of 10 mg/L LAS except that each change occurred about 24 to 48 h later than that of 10 mg/L ( ). In our previous studies 3,4) , g tox of LAS on Daphnia magna was about 50 mN/m. Death ratio of 50 % is expected for both 10 mg/L LAS ( ) and 20 mg/L LAS ( ) when surface tension is 50 ~ 60 mN/m, which corresponds to g tox of LAS under biodegradation.…”
Section: Resultsmentioning
confidence: 99%
“…Following three experiments were conducted for each surfactant: surface tension measurement to study the interfacial activity, HPLC analysis to analyze structural change during biodegradation, and acute aquatic toxicity test using Daphnia magna to study the toxicity. In this study, we used only Daphnia magna for toxicity test, because previous studies 3,4) , in which Oryzias latipes, Daphnia magna, Podocopida, and Artemia salina were used for acute toxicity test, showed that all of the organisms have toxic surface tension (g tox ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Surfactants caused pooled in toxicity affecting the ecosystem and its inhabitants, the toxicity increasing down the trophic levels. The extent of surfactant toxicity is concentration dependant and it varies with season (Marcomini et al 2000 ), prevalence of anaerobic environment (Mungray and Kumar 2009 ), predominance of urban and industrial sewage outlets (Lara-Martin et al 2008 ), distance of sampling points from port of discharge (Gonzalez-Mazo et al 2002 ), occurrence of offshore oil spill or gas exploration, diurnal discharge of sewage (Kantin et al 1981 ), salinity (Lewis 1992 ), hardness of water (Oya et al 2008 ) and presence of adsorbents (Casellato and Negrisolo 1989 ;Marin et al 1994 ). The extend and mode of toxicity is also infl uenced by the chemistry of the pollutant surfactant, its alkyl chain length (Lewis 1991 ) and ethylene oxide (EO) molar ratio (Hall et al 1989 ).…”
Section: Safety Concerns On Surfactantsmentioning
confidence: 99%